2019
DOI: 10.1097/qad.0000000000002218
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and time trends of anal cancer among people living with HIV in Australia

Abstract: Background: Anal cancer incidence increased markedly in people living with HIV (PLWHIV) after the introduction of HAART, but in a few setting settings, recent declines have been reported. We report the incidence and time trends of anal cancer in PLWHIV in Australia. Study design: A data linkage study between the National HIV Registries and the Australian Cancer Database. Methods: Cases of anal squamous cell carcinoma (ASCC) in Australians aged 16 years and above diagnosed with HIV between 1982 and 2012 were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
1
23
0
1
Order By: Relevance
“…Since the first HIV epidemic, the incidence of this neoplasia has increased in seropositive patients, mainly in elderly MSM with AIDS [34]. Recently published data from the Australian HIV and Cancer National Registry showed that the incidence of ASCC rose from 14.8/100,000 people/yr between 1982 and 1995 to 62.1/100,000 people/yr between 2009 and 2012 (p <0.001) [35], similar to the present findings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Since the first HIV epidemic, the incidence of this neoplasia has increased in seropositive patients, mainly in elderly MSM with AIDS [34]. Recently published data from the Australian HIV and Cancer National Registry showed that the incidence of ASCC rose from 14.8/100,000 people/yr between 1982 and 1995 to 62.1/100,000 people/yr between 2009 and 2012 (p <0.001) [35], similar to the present findings.…”
Section: Discussionsupporting
confidence: 89%
“…Both samples were immersed in thinlayer liquid medium and sent to the pathology laboratory of the hospital. Genotypes 16,18,26,31,33,35,39,45,[51][52][53]56,58,59,66,68,73, and 82 were considered to be HR-HPV genotypes. Genotypes 6,11,34,40,[42][43][44]54,55,57,61,[70][71][72]81,83,84, and 89 were considered to be low-risk (LR-HPV) genotypes.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first HIV epidemic, the incidence of ASCC has increased in seropositive patients, mainly in MSM with AIDS [ 17 ]. After the initiation of our screening/treatment program in 2010, the ≥HSIL rate significantly decreased among HIV-infected MSM patients for six years and then subsequently stabilized, with no progression to ASCC in patients with treated HSIL.…”
Section: Discussionmentioning
confidence: 99%
“…Possible involvement of EBV in gastric cancer and precursor lesions [35]; patients with EBV-positive gastric cancer had a better response to chemotherapy and better survival [36] EBV (HHV4) Hepatic EBV infections detected in HCC tissues [37] EBV (HHV4) Lymphoma (DLBCL) EBV RNA detected in B-cell lymphoma samples [38] EBV (HHV4) Lymphoma (PTCL) EBV expression associated with some subtypes of peripheral T-cell lymphomas [39] EBV (HHV4) Oral Higher proportion of EBV-positive oral squamous cell carcinoma in industrialized countries [40] EBV (HHV4) Skin and mucosal EBV DNA frequently detected in skin and mucosal cancers [26] HHV6 Lymphoma (DLBCL) HHV6 RNA detected in B-cell lymphoma samples [38] HHV6 Malignant melanoma HHV6 DNA frequently detected in malignant melanoma [26] HHV7 Bladder HHV7 DNA frequently detected in bladder cancer [26] HHV7 Lymphoma (CTCL) HHV7 DNA frequently detected in cutaneous T-cell lymphoma (Mycosis fungoides) [26] HHV7 Oral HHV7 DNA frequently detected in oral cavity cancer [26] HSV (HHV1/2) Oral Higher proportion of HSV-positive oral squamous cell carcinoma in industrialized countries [40] KSHV (HHV8) Kaposi sarcoma In HIV-infected individuals, KSHV infection is associated with Kaposi sarcoma [41] Polyomaviridae BKV Bladder Possible association of BKV with bladder cancer [26] BKV Colorectal Possible association of BKV with colorectal cancer [42,43], however, other studies found no association [16,44] JCV Colorectal JCV is associated with colorectal cancer [44,45] and may be involved in carcinogenesis [46], specifically in chromosomal instability [47]; JCV Tantigen is expressed in early stage colorectal cancer [48], however, another study found no association [16] MCV Merkel cell carcinoma MCV is the major causative factor for Merkel cell carcinoma [49,50] Retroviridae HIV Anal HIV-positive people have increased risk for anal cancer [51,52] and worse overall colostomy-free survival rates [53] HIV Cervical Cervical cancer...…”
Section: (Hhv5) Colorectalmentioning
confidence: 99%